Validation of the Italian Sense of Agency Scale and Its Relevance to Well-Being: An Iterative Bootstrap Approach - Simone Di Plinio; Claudia Greco; Simone Arnò; Marco Innamorati; Sjoerd J. H. Ebisch (Behavioral Sciences)
The Sense of Agency (SoA) refers to the subjective experience of controlling one’s actions and the external events resulting from those actions. This study aimed to critically evaluate the construct validity, robustness, and clinical utility of the Sense of Agency Scale (SoAS) in an Italian-speaking population, using a data-driven approach to explore potential factor structures. A sample of 992 adults completed the SoAS alongside other validated psychological measures, allowing for a comprehensive analysis of the scale’s psychometric properties. An iterative process of exploratory and confirmatory factor analyses (EFA and CFA) was implemented to assess both two-factor and bifactor models. A refined 10-item version of the SoAS was established, comprising two distinct factors: Sense of Positive Agency (SoPA, five items) and Sense of Negative Agency (SoNA, five items). The results favored a two-factor solution supported by satisfying fit indices, factor loadings, and stability. The revised scale demonstrated strong internal consistency, with McDonald’s omega values of 0.79 (SoNA) and 0.87 (SoPA). This study extends the literature by providing evidence of the scale’s convergent and divergent validity, with significant correlations in the expected directions with constructs such as sense of self, hopelessness, impulsiveness, psychosis-like experiences, and schizotypal traits. These findings support the revised SoAS as a reliable and valid measure for assessing the Sense of Agency and highlight its broader applicability in understanding psychological and psychopathological constructs.